Stellaluna [videorecording (DVD)] - Kowalchuk, William R.; Koretsky, Rachel; Whitestone, Steve; Zanni, Chiara; Pospisil, Eric; Prior, Matthew; Moldowan, Brittany; McNeil, Scott, 1962-; Barr, Kathleen; Crichlow, Brenda; Tockar, Lee; Mankuma, Bill; et al. (MGM kids., 2004)
When the adorable fruit bat Stellaluna is separated from her mother, she is adopted by a family of birds, but soon finds that she just can't fit in. Her playmates like to sleep at night; she wants to fly. They whistle and sing; she doesn't even have a beak! But just when it seems like she'll always be an outsider, Stellaluna makes an amazing discovery. Now she'll learn to cherish the things that make her different from everyone else. And she'll see that an open mind and an open heart can lead to the greatest gift of all.